2017
DOI: 10.1007/s12186-016-9171-6
|View full text |Cite
|
Sign up to set email alerts
|

The Learning Potential of Boundary Crossing in the Context of Product Introduction

Abstract: The aim is to explore challenges related to the integration between product development and production in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…The identified strategies in the present study to counterbalance discontinuities between the practices of school and work are similar to bridging strategies found in other studies. Relating to (dis)continuity between two work practices, a study in the context of product introduction showed that integration of product development and production can be enhanced by intrapersonal and interpersonal boundary crossing (Gustavsson & Säfsten, 2017). Our study further enriches these insights by taking a specific design perspective and by including the institutional level.…”
Section: Conclusion and Discussionmentioning
confidence: 52%
“…The identified strategies in the present study to counterbalance discontinuities between the practices of school and work are similar to bridging strategies found in other studies. Relating to (dis)continuity between two work practices, a study in the context of product introduction showed that integration of product development and production can be enhanced by intrapersonal and interpersonal boundary crossing (Gustavsson & Säfsten, 2017). Our study further enriches these insights by taking a specific design perspective and by including the institutional level.…”
Section: Conclusion and Discussionmentioning
confidence: 52%
“…The findings revealed that persons who acted as brokers both served as and created the cross-boundary connections necessary to develop the coaching methods and secure the future financing to build a more permanent organization founded on the WPDP (c.f. Gustavsson and Säfsten, 2017;Long et al, 2013;Wenger, 1998). These persons acted as brokers at multiple WPDP levels (Filip et al, 2016) with different primary agendas at each levels (operative, strategic and national).…”
Section: Discussionmentioning
confidence: 99%
“…When brokers collaborate across boundaries to build cross-boundary connections, they learn, and their learning can set organizational change in motion (Akkerman and Bruining, 2016;Engeström et al,1995;Gustavsson and Säfsten, 2017;Wenger, 2000).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…boundaries, such as R&D and manufacturing (Carlile 2002(Carlile , 2004. Boundary objects are interpreted differently by the actors that belong to different boundaries, and it is an acknowledgement and discussion of these differences that ensure establishment of shared understanding (Bechky 2003;Gustavsson and Säfsten 2017). To be effective the boundary objects need to possess certain features such as providing shared language and concrete means of translating and learning about the differences and interdependencies between the actors (Dougherty 1992;Majchrzak, More, and Faraj 2012).…”
Section: Communication Challenges and Use Of Visual Representationsmentioning
confidence: 99%
“…Shorter product life cycles, intense competition, the diverse geographic location of R&D teams and manufacturing sites, and globally distributed suppliers are a reality for many manufacturing companies today (Gustavsson and Säfsten 2017). Therefore, the geographical distribution among actors involved in NPD projects has the tendency to amplify communication challenges (e.g.…”
Section: Introductionmentioning
confidence: 99%